Hashimoto encephalopathy: a case report and a short revision of current literature: Hashimoto encephalopathy in pediatric age - Chiarello, Paola; Talarico, Valentina; Nicoletti, Angela; Rodio, Benedetta; Arcuri, Pier Paolo; Bosco, Domenico; Gigliotti, Francesco; Galati, Maria Concetta; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Hashimoto encephalopathy (HE) is a rare but controversial entity encompassing a variety of neuropsychological presentations in the setting of autoimmune thyroid disease. HE, mostly described in adults, with a female‑to‑male ratio of 4:1, is a relatively rare entity in the pediatric population and probably under recognized as a cause of acute encephalopathy in children and adolescents. A number of pathogenetic mechanisms have been suggested. Female prevalence, presence of autoantibodies, fluctuating course, and response to immunomodulatory therapy suggest the autoimmune nature of the disease. Existing diagnostic criteria for adults require modification to be applied to children and adolescents, who differ from adults in their clinical presentations, clinical findings, autoantibody profiles, treatment response, and long-term outcomes. A combination of neurological findings, positive antithyroid autoantibodies, and responsiveness to steroids is diagnostic of HE. We add a new case of HE in an adolescent girl and review the current HE literature.